Sistemas de informações geográficas e a gestão municipal brasileira contemporânea - Elaiz Aparecida Mensch Buffon; Geisa Tamara Bugs; Clovis Ultramari (Confins)
This article discusses one of the attributes concerning the use of GIS by Brazilian municipalities. To do so, the research initiates an extensive primary data collection from the entire universe of Brazilian municipalities. This investigation is followed by a more qualitative exercise – interviews with key agents in the institutional framework of one specific municipality: Pato Branco, Paraná, Brazil. The main conclusions are 1.88% of the websites of municipalities in Brazil have interactive GIS maps, and 50.48% are linked to urban planning. The total population of the municipality was reflected in the municipalities that presented interactive maps in GIS on the website. In addition to the diagnosis, the study details a project to create a support room for integrated management in Pato Branco City Hall (SAGI-PB). With this, the work reinforces the need to create programs and projects at state and federal level to support the expansion of the use of GIS in Brazilian municipalities.